Share and strife: the strait of Melaka and the portuguese (16th and 17th centuries) - Pinto, Paulo Jorge de Sousa (2014)
The Strait of Melaka is the longest strait in the world, stretching for about 800 km from the northern tip of Sumatra to Singapore. It exhibits a dual character like no other, being simultaneously a privileged linking passage of two seas and two knots of human civilization – India and China – and a »bottleneck« that constrains the maritime connections between them. Today, the latter aspect is globally dominant. The strait is considered and analysed mostly as an obstacle rather than a linking point: how to reach China from the West or elsewhere is no longer an issue, but securing the vital flows that pass into the strait on a daily basis undoubtedly is. Accidents, natural catastrophes, political local crises or terrorist attacks are permanent dangers that could cut this umbilical cord of world trade and jeopardize a particularly sensitive and vulnerable area; piracy and pollution are the most common local threats and vulnerabilities.